Acronym for an object oriented architecture - Muñoz Escalante, Mauricio (Estoa. Journal of the Faculty of Architecture and Urbanism, 2019)
The main purpose of this essay is to promote a reflection on architectural objects apropos Graham Harman, Manuel DeLanda, Bruno Latour and other philosophers’ loosely associated theory about objects on actual culture. It presents how architecture objects were already present from a modern previous perspective, as well as its intrinsic object-subject relation, and then it analyzes how a flat ontology, as proposed by Object Oriented Ontology, changes paradigms such as the whole as sum of its parts, and the correlation between human beings and objects, among others. It supports the idea that the existence of objects despite its relations produces an endless amount of images or appearances, while the object-in-itself remains inaccessible to us. Accordingly, it finally speculates that an acronym containing such multiplicity would also be impossible.